A catalytic regioselective procedure for the synthesis of aryl oximes in the presence of palladium nanoparticles. Issue 11 (2nd November 2022) - Demir, Emine; Orhan, Ersin; Goksu, Haydar
Abstract: The synthesis of aryl oximes from aryl aldehyde derivatives was carried out using hydroxylamine hydrochloride and aluminum oxy hydroxide-supported palladium (Pd/AlO(OH) nanoparticles. The procedure is revealed via the regioselective synthesis of oxime derivatives in a polar solvent mixture resulting in high yields at room temperature. Graphical Abstract: UF0001